Diagnostic Value of Saliva RT-PCR Test within Suspected SARS-CoV-2 Cases in Indonesia - Putra, Andika Chandra; Zaini, Jamal; Ridwanuloh, Asep Muhammad; Nugroho, Herjuno Ari; Setyawan, Ryan Haryo; Idris, Idris; Setiawan, Ruby; Sushadi, Pangda Sopha; Wulandari, Ari Sulistyo; Zannati, Anky; Indriawati, Indriawati; Erdayani, Eva; Wahyuni, Wahyuni; Agustiyanti, Dian Fitria; Wisnuwardhani, Popi Hadi; Saniyyah, Zahrah; Azika, Wira Norman; Haryanto, Budi; Utomo, Ahmad Rusdan Handoyo; Ningrum, Ratih Asmana (Health and Medical Journal, 2024)
Introduction: The ongoing SARS-CoV-2 pandemic has profoundly emphasized the pressing need for accurate and reliable diagnostic procedures. Given the potential health risks associated with nasopharyngeal swabs, there has been growing interest in seeking alternative diagnostic mediums. In this context, our study delved into evaluating saliva as a potential diagnostic tool, simultaneously assessing its efficiency in relation to patient demographics and their exhibited clinical symptoms. Methods: Spanning from May to December 2020, we conducted a comprehensive cross-sectional analysis. We meticulously examined medical records to gather insights on patient characteristics, existing health conditions, onset of symptoms, clinical manifestations, and compared the results obtained from both salivary and nasopharyngeal RT-PCR tests for SARS-CoV-2. Results: Among the individuals suspected of SARS-CoV-2 infection, the mean age stood at 52.4 years, with males representing 60.3% of this group. Interestingly, a significant 76.9% reported underlying health conditions, predominantly hypertension and diabetes. The most commonly reported symptoms encompassed respiratory challenges, notably coughing and shortness of breath, succeeded by symptoms like nausea, fever, and a general sense of fatigue. The performance of saliva tests, in terms of accuracy, appeared to be significantly influenced by the timing of symptom emergence. Conclusion: The RT-PCR tests utilizing saliva samples demonstrated considerable promise, especially during the early stages of symptom manifestation, providing a reliable alternative to traditional nasopharyngeal swabs. The findings suggest a superior diagnostic sensitivity when utilizing saliva during the initial phases of a SARS-CoV-2 infection.